Transmissibility of Mycobacterium pinnipedii in a murine model - Marfil, María Jimena; Blanco, Federico Carlos; Colombatti Olivieri, María Alejandra; Eirin, María Emilia; Zumárraga, Martín José (Frontiers in Cellular and Infection Microbiology, 2024)
The causative agent of tuberculosis in pinnipeds is Mycobacterium pinnipedii, a member of the Mycobacterium tuberculosis complex (MTC). The natural hosts are pinnipeds; however, other non-marine mammals, including humans, can also be infected. The transmissibility of a pathogen is related to its virulence. The transmissibility of a M. pinnipedii strain (i.e., 1856) was investigated in a murine model and compared with that of two Mycobacterium bovis strains (i.e., 534 and 04-303) with different reported virulence. Non-inoculated mice (sentinels) were co-housed with intratracheally inoculated mice. Detailed inspection of mice to search for visible tuberculosis lesions in the lungs and spleen was performed, and bacillus viability at 30, 60, and 90 days post-inoculation (dpi) was assayed. A transmissibility of 100% was recorded at 30 dpi in sentinel mice co-housed with the inoculated mice from the M. pinnipedii and M. bovis 04-303 groups, as evidenced by the recovery of viable M. pinnipedii and M. bovis from the lungs of sentinel mice. Mice inoculated with M. pinnipedii (1856) and M. bovis (534) survived until euthanized, whereas five of the M. bovis 04-303-inoculated mice died at 17 dpi. This study constitutes the first report of the transmissibility of a M. pinnipedii strain in mice and confirms the utility of this experimental model to study virulence features such as the transmission of poorly characterized MTC species.